Mat, makt och motstånd: Om konflikter inom tvångsvård - Tove Pettersson (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract This article discusses how food constitutes a source of conflict at locked compulsory care institutions for youth and adults. The conflicts that arise are often about where, when and what one is allowed to eat, and can have serious consequences such as isolation of the inmate. Both the inmates and the staff describe these conflicts as being about »small things«. But while the staff maintains this level of interpretation, stories from the  inmates reveal that in the context of the total institution, these »small things« can be very significant. The rules regarding food are both a reminder of the loss of the outside world and evidence of the loss of control and power that comes with confinement. The results show that younger inmates are more thoroughly controlled than their older counterparts in several respects.